Investigating technology users' behavior and difficulties in two different multilingual contexts - da Rosa, Diego Moreira; Guedes, Leandro Soares; Landoni, Monica; Silveira, Milene (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
The popularization of computing devices and internet access, especially in developing countries, has driven attention to an increasing number of software users with varied cultural and linguistic backgrounds. Human-Computer Interaction research has thus far considered language communities as static and isolated entities, generally associating them with a specific country. Linguists know, however, that cultures interact and exchange ideas, languages spread across state borders, and individuals often speak two or more languages. For an effective HCI design, developers should consider these social and individual aspects of multilingualism. In this study, we aim to investigate technology users' behavior and difficulties in different multilingual contexts. An online survey has been conducted with multilingual students from two universities: one in Switzerland and the other in Brazil. Analysis of 196 valid responses confirms a high level of multilingualism in general, but higher among students in Switzerland. The types of tasks and the language-related issues reported by the participants varied between the two contexts, indicating that the level of multilingualism impacts users' behavior online. A final discussion summarizes challenges and opportunities for future studies aiming to propose HCI design approaches with a focus on multilingualism.